Pengaruh Brand Image dan Electronic Word Of Mouth (E-WOM) terhadap Keputusan Pembelian Smartphone Samsung di Kota Malang - Oktaviani, Fadhilah Nur; Zagladi, Arief Noviarakhman (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the influence of Brand Image and Electronic Word of Mouth (E-WOM) on purchasing decisions for Samsung smartphones in Malang City. This study uses a quantitative method with an explanatory research approach to explain the relationship between variables. The population of the study was Samsung smartphone users in Malang City with a sample of 73 respondents selected using the purposive non-probability sampling method. Data analysis was carried out by testing validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination test. The results showed that Brand Image had a significant effect on purchasing decisions with a significance value of 0.000 (<0.05), while E-WOM did not have a significant effect on purchasing decisions with a significance value of 0.060 (>0.05). These results indicate that a strong brand image is the main factor in driving Samsung smartphone purchasing decisions, while the influence of E-WOM tends to be lower because consumers rely more on personal experience in their purchasing decisions. This study provides implications that companies need to strengthen their brand image by emphasizing product quality, technological innovation, and after-sales service to increase consumer trust and loyalty. In addition, E-WOM-based marketing strategies still need to be optimized to be more effective in influencing consumer purchasing decisions. Keywords: Brand Image, Electronic Word of Mouth (E-WOM), Purchasing Decision, Samsung Smartphone